Analisis Tingkat Gaji pada Kinerja Guru di MIS Muslimin Cihurang - Muhammad Deka Faathir; Fizi Fauziya (EKONOMIKA45 : Jurnal Ilmiah Manajemen, Ekonomi Bisnis, Kewirausahaan, 2024)
Teacher performance has a very important role in determining the success of a school in achieving its goals. Teacher performance is influenced by various factors, both external and internal. One of the internal factors that is thought to have a close relationship with teacher performance is the level of salary earned. There are many teachers at MIS Muslimin Cihurang who have honorary teacher status and therefore have salary levels that do not match the workload they carry. The aim of this research is to determine the level of salary for teacher performance at MIS Muslimin Cihurang. This research uses a qualitative approach. Observation, interview and documentation methods were used to collect data, with data analysis techniques including data reduction, data presentation and drawing conclusions. Based on the research results, it shows that although the level of teacher salary at MIS Muslimin Cihurang is sufficient to meet living needs, it still has not reached the level expected to achieve teacher welfare. Nevertheless, there is still strong intrinsic motivation among teachers, namely they have quite high work motivation, especially because of a sense of responsibility to educate the nation's children. Teacher performance is also reflected in their ability to plan, implement and evaluate learning. Teachers continue to try to give their best and carry out structured evaluations even though there are obstacles in the learning process. Therefore, increasing teacher salaries at MIS Muslimin Cihurang can increase motivation and job satisfaction, which has an impact on improving the quality of learning and teacher performance.